IMPLEMENTASI MARKETING MIX DALAM TABUNGAN BARATA iB BANK BTN SYARIAH KCPS PAREPARE - Anugrah Perdana; Abdul Hamid; Arqam Arqam (Institut Agama Islam Negeri Parepare, 2019)
Syariah bank BTN KCPS parepare is a bank that supply batara savings ib which make them customers to save , this product is very attractive to the community .To quantity bank in indonesia has up and each bank had to be able to having the power of its own , both the public service , innovative products to stay in business and stable .This study aims to to know the implementation of marketing mix in batara ib on kcps parepare syariah bank btn .The research was conducted in syariah bank btn kcps parepare with a kind of qualitative research was conducted by adopting both fenomenology and in collect the primary data used method of interviews and observation .As for tekhnik analyzing of inductive around. This research result indicates that , the implementation of the program and the implementation of the marketing mix in syariah bank btn kcps parepare applied to all elements videlicet; product , price , place , promotion , people , physical evidence , processe.